Identification of the vigour test to predict planting value of chickpea seeds - MUKESH KUMAR; SHIV K. YADAV; S. PANDEY; A. K. VARI; R. YADAV; J. KUMAR (Seed Research, 2026)
The studies were conducted on various seed vigour parameters, including accelerated ageing test and electrical conductivity of seed leachate in relation to field emergence and storability of chickpea (Cicer arietinum). The materials for study constituted of two seed lots i.e. freshly harvested and four years old. Each lot consisted of two genotypes each from desi (Pusa 256 and Pusa 2028) and kabuli (Pusa 1053 and Pusa 1108) types. Inter-varietal and inter-ageing differences were observed for the vigour parameters amongst the eight different chickpea seed lots. The results on each variety for various seed parameters and vigour tests revealed significant differences for test weight, seed coat weight, first count, germination per cent, abnormal seedling, vigour index I and vigour index II. The electrical conductivity values were found significantly high in old seed lot. Accelerated ageing test conducted at 40°C and 100% RH for period of 36 hrs gave significant differences between kabuli varieties. Electrical conductivity was significantly correlated with most of vigour parameters studied, while the accelerated ageing test and the first count also gave significant correlation with the field emergence. Thus, the electrical conductivity test could be suggested as 'The Vigour Test' for chickpea.